(untitled) (Heritage, 2020)
Migration trends have existed throughout human history, with the primary reasons for leaving one’s territorial or ethnic community to seek a better life or escape from persecution and violent conflict. Unlike legal migration, which takes place under the laws of the country of origin of the migrant and the country of destination, there are also illegal migrations that reflect special circumstances and mean any movement of population from the territory of one country to the territory of another that does not take place under the regulations of those countries, and also the stay of aliens in a particular country in a manner inconsistent with its legislation. Therefore, the aim of this paper is to analyze the security aspects of migration processes in the EU process.